The VMC survey. XVIII. Radial dependence of the low-mass, 0.55-0.82 Mo stellar mass function in the galactic globular cluster 47 Tucanae - Zhang, Chaoli (2015)
We use near-infrared observations obtained as part of the Visible and Infrared Survey Telescope for Astronomy (VISTA) Survey of the Magellanic Clouds (VMC), as well as two complementary Hubble Space Telescope (HST) data sets, to study the luminosity and mass functions (MFs) as a function of clustercentric radius of the main-sequence stars in the Galactic globular cluster 47 Tucanae. The HST observations indicate a relative deficit in the numbers of faint stars in the central region of the cluster compared with its periphery, for 18.75 ≤ m F606W ≤ 20.9 mag (corresponding to a stellar mass range of 0.55 < m ∗ /M o < 0.73). The stellar number counts at 6.′7 from the cluster core show a deficit for 17.62 ≤ m F606W ≤ 19.7 mag (i.e., 0.65 < m ∗ /M o < 0.82), which is consistent with expectations from mass segregation. The VMC-based stellar MFs exhibit power-law shapes for masses in the range 0.55 < m ∗ /M o < 0.82. These power laws are characterized by an almost constant slope, α. The radial distribution of the power-law slopes α thus shows evidence of the importance of both mass segregation and tidal stripping, for both the first- and second-generation stars in 47 Tuc.